For a pedagogical contribution between the ethnology narrative and some situations in healthy life - José Siles González; Eva María Gabaldón Bravo; David Molero Tolino; Yolanda Gallardo Frías; Encarnación García Hernández (Universidad de Alicante, 1997)
Narrative is a gender form in which characters express themselves with no other limit than that imposed by the author himself. The purpose of the present research is the use of narrative as a means of better understanding the diverse situations faced by people within the immense framework of health and illness. It is within the boundaries of this context that the narrative and poetic work of Benedetti reveals its pedagogical and anthropological potential. Our present study takes advantage of the poet's narrative material as a vehicle with which one may interpret situations of health versus illness, where moods, sensations, feelings, expectancies, fears, hopes and knowledge all meet.